Can market structure explain cross-country differences in health? - Rybczynski, Kate; Curtis, Lori (Farmeconomia. Health Economics and Therapeutic Pathways, 2013)
There is a well documented health disparity between several European countries and the United States. This health gap remains even after controlling for socioeconomic status and risk factors. At the same time, we note that the U.S. market structure is characterized by significantly more large corporations and "super-sized" retail outlets than Europe. Because big business is hierarchical in nature and has been reported to engender urban sprawl, inferior work environments, and loss of social capital, all identified as correlates of poor health, we suggest that differences in market structure may help account for some of the unexplained differences in health across Europe and North America. Using national level data, this study explores the relationship between market structure and health. We investigate whether individuals who live in countries with proportionately more small business are healthier than those who do not. We use two measures of national health: life expectancy at birth, and age-standardized estimates of diabetes rates. Results from ordinary least squares regressions suggest that, there is a large and statistically significant association between market structure (the ratio of small to total businesses) and health, even after controlling income, public percent of health expenditure, and obesity rates. This association is robust to additional controls such as insufficient physical activity, smoking, alcohol disease, and air pollution.